Hurricane debris and damage assessment for Florida urban forests (2009)
A random 10% sample of communities in highly-impacted counties from the 2004 and 2005 Florida, U.S. hurricane seasons were used to study tree debris generation and damage from seven hurricanes. Woody debris amounts in cubic meters (m3 ) (cubic yards; yd3 ) as well as rates and costs for cleanup, tree removal and pruning were obtained for these events. Average debris generation per 30.5 m (100 ft) of street segment ranged from 0.59 m3 (0.77 yd3 ) for low damage, 3.4 m3 (4.44 yd3 ) for moderate damage, and 17.47 m3 (22.85 yd3 ) for high damage levels; cost of removal and disposal averaged $28.25 per m3 ($21.47 per yd3 ). Most communities used unit costing to account for tree removal and pruning rates, averaging 2% and 28% of street trees, respectively. Tree canopy, wind speed, and percentage of urban developed land all had a significant effect on debris amount. Florida communities with a greater tree density generated decreased amounts of debris during the 2004 and 2005 hurricane season. These results can be used to help communities plan for hurricane management activities and estimate potential damages to their tree resource.